Screening of lipids and kidney function in children and adolescents with Type 1 Diabetes: does age matter? - Catamo, Eulalia; Robino, Antonietta; Dovc, Klemen; Tinti, Davide; Tamaro, Gianluca; Bonfanti, Riccardo; Franceschi, Roberto; Rabbone, Ivana; Battelino, Tadej; Tornese, Gianluca (Frontiers in Endocrinology, 2023)
Introduction: The purpose of this study was to evaluate lipid profile and kidney function in children and adolescents with Type 1 Diabetes. Methods: This was a retrospective study including 324 children and adolescents with Type 1 Diabetes (48% females, mean age 13.1±3.2 years). For all participants, demographic and clinical information were collected. The prevalence of dyslipidemia and kidney function markers were analysed according to age. Multivariate linear regression analyses were performed to test the association of lipids or markers of renal function with demographic and clinical information (gender, age, disease duration, BMI SDS, HbA1c). Results: In our study the rate of dyslipidemia reached 32% in children <11 years and 18.5% in those ≥11 years. Children <11 years presented significantly higher triglyceride values. While the albumin-to-creatinine ratio was normal in all individuals, 17% had mildly reduced estimated glomerular filtration rate. Median of HbA1c was the most important determinant of lipids and kidney function, being associated with Total Cholesterol (p-value<0.001); LDL Cholesterol (p-value=0.009), HDL Cholesterol (p-value=0.045) and eGFR (p-value=0.001). Conclusions: Dyslipidemia could be present both in children and adolescents, suggesting that screening for markers of diabetic complications should be performed regardless of age, pubertal stage, or disease duration, to optimize glycemia and medical nutrition therapy and/or to start a specific medical treatment.